Case report: Creutzfeldt-Jakob disease: a case that initiated with the onset of obsessive-compulsive state - Li, Baizhu; Wang, Shan; Han, Shiyu; Hu, Ning; Shang, Xiuli (Frontiers in Neurology, 2023)
Background Obsessive-compulsive disorder (OCD) is a common reason for patients to seek symptomatic treatment in psychiatric departments, which makes it challenging to consider underlying organic nervous system diseases. However, Creutzfeldt-Jakob disease (CJD) can present with atypical symptoms, sometimes even as initial symptoms, leading to misdiagnosis or missed diagnosis. Lumbar puncture and brain DWI are important diagnostic methods for CJD, and the detection of 1,433 protein can be performed to confirm the diagnosis. Case presentation We present the case of a 63-year-old woman who was initially diagnosed with obsessive-compulsive disorder in 2022. Despite seven months of symptomatic treatment, her symptoms did not improve. She also developed symptoms of altered consciousness, such as upper limb tremors and mutism. Based on brain DWI and positive results from the detection of 1,433 protein, she was ultimately diagnosed with CJD. Conclusion Creutzfeldt-Jakob disease (CJD) can manifest initially as obsessive-compulsive disorder (OCD) with atypical symptoms, making it prone to misdiagnosis. Therefore, it is crucial to conduct further investigations, including lumbar puncture and imaging, to exclude organic nervous system diseases before initiating symptomatic treatment for psychiatric disorders. This approach can facilitate early diagnosis of CJD and other potential organic neurological diseases.